Physiological bases of human performance during work and exercise (Elsevier, 2008)
Physiological Bases of Human Performance during Work and Exercise is a high-level physiology text for advanced students, researchers and practitioners in the fields of human physiology, exercise science and applied physiology. Eighty internationally recognised scientists from sixteen countries have written chapters within six areas: - Physiological performance limits and human adaptation; - The physiological bases of gender differences in performance; - Age and human performance; - Performance under environmental extremes; - Exercise and health interactions; and - Optimising performance through supplementation. Each section contains state-of-the-art reviews of the scientific literature. To stimulate critical thinking, there are thirteen debates and discussions that focus on some of the controversial topics that exist across these disciplines.